Promoting Effect of Nitride as Support for Pd Hydrodechlorination Catalyst - Hua, Xiaotian (Langmuir : the ACS journal of surfaces and colloids, 2023)
Pd-catalyzed reductive decontamination is considerably promising in the safe handling of various pollutants, and previous studies on heterogeneous Pd catalysts have demonstrated the key role of support in determining their catalysis performance. In this work, metal nitrides were studied as supports for Pd as a hydrodechlorination (HDC) catalyst. Density functional theory study showed that a transition metal nitride (TMN) support could effectively modulate the valence-band state of Pd. The upward shift of the d-band center reduced the energy barrier for water desorption from the Pd site to accommodate H2/4-chlorophenol and increased the total energy released during HDC. The theoretical results were experimentally verified by synthesizing Pd catalysts onto different metal oxides and the corresponding nitrides. All studied TMNs, including TiN, Mo2N, and CoN, showed satisfactorily stabilized Pd and render Pd with high dispersity. In line with theoretical prediction, TiN most effectively modulated the electronic states of the Pd sites and enhanced their HDC performance, with mass activity much higher than those of counterpart catalysts on other supports. The combined theoretical and experimental results shows that TMNs, especially TiN, are new and potentially important support for the highly efficient Pd HDC catalysts